2021
DOI: 10.3389/fmedt.2021.724089
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cardio-Ankle Vascular Index and Left Atrial Phasic Function in Hypertensive Patients With Preserved Ejection Fraction

Abstract: Background: To investigate the relationship between arterial stiffness, reflected by cardio-ankle vascular index (CAVI) value, and left atrial (LA) phasic function in hypertensive patients with preserved left ventricular ejection fraction (LVEF).Methods: We retrospectively studied 165 consecutive patients (mean age, 66.5 ± 11.7 years) diagnosed with hypertension with preserved LVEF who had undergone CAVI measurement and echocardiography on the same day. The latter included speckle-tracking echocardiography to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Namba et al also found no link between the CAVI and LAD (47). These results were similar in patients with HT and HFpEF based on HT (48)(49)(50).…”
Section: Involvement Of the Cardio Ankle Vascular Index (Cavi) In Ht ...mentioning
confidence: 78%
“…Namba et al also found no link between the CAVI and LAD (47). These results were similar in patients with HT and HFpEF based on HT (48)(49)(50).…”
Section: Involvement Of the Cardio Ankle Vascular Index (Cavi) In Ht ...mentioning
confidence: 78%
“…Cardiovascular interaction has recently been demonstrated using CAVI, not only in the left heart system but also in the right heart system. 9,10 Recently, much evidence has been reported on SGLT2 inhibitors and ARNI for heart failure. [11][12][13] However, there has not yet been a report using CAVI that focuses on effects of the "Fantastic Four" on the cardiovascular interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the concept of cardiovascular interaction was proposed using CAVI. [10][11][12] CAVI reflects smooth muscle cell contraction and relaxation. As for the effects on BP and CAVI, in the present case, when the sacubitril/valsartan dose was tapered from 400 mg to 200 mg, CAVI increased without any changes in cardiac function, such as global longitudinal strain (Table 1).…”
mentioning
confidence: 99%